Pengaruh Right Issue Saham Terhadap Kinerja Keuangan Pt Bank Rakyat Indonesia (PERSERO) TBK - Rizki Fahreza; Audi Tomy Reriya Sakti (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
Companies that have previously listed their shares on a stock exchange may consider issuing the right shares as an additional capital-raising method to expandtheir operations. Investors need to have a solid understanding of both the current state of the firm and the nature of the rights issue before they can proceed with the redemption of their rights. In September of 2021, one of the Indonesian banking issuers, PT Bank Rakyat Indonesia (Persero) Tbk, carried out a rights issue toraise capital to lay the groundwork for forming an Ultra Micro SOE Holding business in Indonesia. As a result, this research aims to investigate the qualities of companies via the use of fundamental analysis, namely by examining profitability ratios, solvency ratios, and other supporting ratios. The purpose of this research is to establish whether or not the outcomes of this business activity have a favorable impact on the firm. Calculations and analyses are carried out using secondary data in the form of the financial statements of PT Bank Rakyat Indonesia (Persero) Tbk for 2018-2022. This data is used as a reference in the research approach. According to the findings of this study, the financial performance of PT Bank Rakyat Indonesia Tbk, based on fundamental analysis, is in excellent shape and has witnessed growth following the Covid-19 epidemic. These findings are shown by the fact that the company has a positive outlook. Because the price is lower than the market price and the Price-to-Earnings Ratio is decreasing, BBRI's simulation of a rights issue calculation results reveal an appealing valuation. This is the case because the price is lower than the market price.